Tổ chức dạy học môn Toán lớp 4 theo định hướng phát triển năng lực số cho học sinh tiểu học - Nguyễn, Kim Yến; NGUYỄN, THỊ ĐÀO KIM; Lê, Tiến (Tạp chí Giáo dục, 2026)
In the context of digital transformation in education, developing digital competence for primary school students is essential to meet the requirements of the 2018 General Education Curriculum. This study uses document and content analysis to clarify the theoretical basis of digital competence, the digital competence framework for primary school students, and its integration into Grade 4 Mathematics teaching. By aligning Mathematics learning outcomes with digital competence indicators, the article proposes teaching orientations for topics such as numbers and operations, geometry and measurement, statistics and probability. It also presents a five-step teaching process, illustrated through the lesson “Statistical Data Sets”. The findings provide theoretical and practical suggestions for teachers to design and organize Mathematics activities that develop students’ digital competence.